(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Finding the College right for you is an Exciting and, at times, Challenging Experience for B. Tech. Course after Higher Secondary Diplomas (10th. + Diplomas) and Senior Secondary (10th. + 2). With So Many Choices, You may likely wonder where to begin. A Good First Step is to tailor your Choices Based on which Colleges Offer the Various Streams in B. Tech. Course that Best Match Your Interests. The objective of study is to scrutinize how various aspects have encouraged on the decision of students’ in selecting self-finance institute for the B.Tech. Course in Uttar Pradesh. For Detail Analysis, the Questionnaire has been developed highlighting the factors which can affect Institute selection decision of Self-Finance Institute for Bachelor Degree i.e. B.Tech. Degree in Uttar Pradesh (U.P.). The Study has been carried out by using Convenience Sampling under Non-Probability Sampling Method of Descriptive Research Design. The studies have been carried out with sample of about 300 students’ in various districts in U. P. State. Study has been carried out by using Primary Data through Personal Interview of students’. Personal Interview has been conducted through Questionnaire.